A Challenging Case of Limb Salvage Requiring a Combination of Composite Fixation and Masquelet Technique to Address Significant Segmental Bone Loss - C. Blair; A. T. Simela; B. J. Cross (Case Reports in Orthopedics)
Cases of limb salvage following skeletal trauma involving significant bone loss pose a particular challenge to the reconstructive surgeon. Certain techniques for addressing this complex issue have been advanced in recent years and have met with considerable success. The Masquelet technique involves a staged procedure in which a temporary skeletal stabilization is paired with implantation of an antibiotic spacer and left in place for 6–8 weeks, during which time a “pseudomembrane” forms around the cement spacer. During the second stage of the procedure, the pseudomembrane is incised, the antibiotic spacer removed, and bone graft is placed. We present a case of significant segmental femur loss in a 19-year-old male opting for limb salvage in which a 17-centimeter segmental loss of bone was essentially regrown using a combination of the Masquelet technique with supplemental endosteal fixation.